Economic unit: incorrect notification at the subsidiary’s domicile when the addressee is the parent company. Commentary to the CJEU of 11 July 2024, Volvo v. Transsaqui - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
In the judgment under analysis, the Court of Justice answers a question referred for apreliminary ruling concerning the correct, or not, notification of the claim in civil liability proceedings for damages arising from the truck cartel. In the case, the applicant company claims compensation from Volvo for the damage it has suffered as a result of the payment of an overcharge for the purchase of two Volvo trucks. The victim brought an action before Valencia Commercial Court No 1 against the parent company Volvo, whose registered office is in Sweden. However, on the ground that Volvo and the Spanish subsidiary of the brand were economically united because the latter was wholly owned by the former, service was effected at the address of Volvo’s Spanish subsidiary. The Court considers that, without calling into question the existence of economic unity, each entity has its own independent legalpersonality and, therefore, if the parent company is sued, it must be served at its domicile, in Sweden.
Keywords: truck cartel; civil liability for damages arising from European Antitrust Law infringements; economic unit; Regulation 2020/1784